Pendidikan Karakter di Sekolah (Studi Penyimpangan Siswa di Mts Muhammadiyah Tallo) - Suardi Suardi; Megawati Megawati; Hasnah Kanji (Universitas of Muhammadiyah Makassar, 2018)
The main problem in this study is that Tallo MTs Muhammadiyah is a religion-based school, but students often make irregularities that do not reflect the religious character of the school's characteristics. The research method used is a qualitative method and determines the informant by purposive sampling. The technique of analyzing data is through various stages, namely data reduction, data analysis, and conclusion drawing. While the data validity technique uses source, time, method triangulation. The results of the study show that character deviations occur due to (1) social environment factors, family economic factors, and personality factors or character of the students themselves. (2) Forms of student irregularities, namely truancy, smoking in class, violations of discipline such as using a cellphone while studying, using language that is not polite, using clothes that are not neat, and going out / leaving without permission honest, disciplined, religious, and responsible. (3) Implications for learning, namely the principal increases discipline, both teacher and student views and achievements that are not good for students who often do deviations. (4) School efforts by providing understanding and exposure to students about moral values in life (moral knowing) and providing motivation to instill confidence and enthusiasm for achievement (moral feeling) and carry out activities based on character education (moral behavior / action.Keywords: Education, Character, Student Deviation